Academic Discourses On Women In The Context Of Islamic Law: A Bibliometric Approach - Okur, Hüseyin; Cançelik, Ali; Duran, Büşra Nur; Aşar, Betül (De Jure: Jurnal Hukum dan Syari'ah, 2025)
This study aims to comprehensively evaluate the temporal trends of the literature, academic collaborations, and the most cited works in the field of Islamic law and women by employing a bibliometric analysis method. For the sample scope of the study, academic articles indexed in the Web of Science database between 2003 and 2023 were analysed. The findings indicate that research on Islamic law and women is concentrated in specific geographical regions, interdisciplinary approaches have been increasingly adopted, and periodic fluctuations are observed in academic production. The results reveal that the highest academic output is produced in countries such as the United States, Turkey, Malaysia, Indonesia, and the United Kingdom. However, despite Turkey’s high publication productivity, its international citation rates remain low. A significant portion of the studies focuses on the intersection of gender and legal perspectives. Mir-Hosseini’s work, with 130 citations, is the most frequently referenced article. Another notable finding is the limited academic collaboration in the field of Islamic law, as most studies are conducted as individual research endeavours. The findings suggest that the issue of women's rights within the context of Islamic law requires more interdisciplinary studies and that academic production should enhance its international visibility. Future research is recommended to incorporate empirical datasets, integrate studies in local languages into the international academic literature, and increase regional comparisons. This study offers a valuable resource for understanding the intellectual structure of academic production on Islamic law and women, and aims to serve as a guide for future research.